Studi Pengaruh Pembebanan sebagai Dasar Scheduling Maintenance untuk Meminimalisir Susut Umur Transformator 1 GI Blimbing - Ahmad Hermawan; Rachmat Sutjipto; Shafira Irmadhani Hidayat; Florentina Berlian Suryaningtyas (Elposys: Jurnal Sistem Kelistrikan, 2020)
Transformer 1’s load in Blimbing Substation has increased significantly each year. In 2016 until 2018 the load on Transformer 1 was 33.81%, 43.53%, and 71.75%. The amount of this transformer’s load will affect the hot spot temparature. Hot spot temperature is also affected by environmental temperature. In this study, load curve method was used then followed by calculate the loss life of transformer. From the calculation, known that the higher of hot spot temperature, the higher impact to loss life of transformer too. In 2018, the highest loading data was on November and it was obtained loss life of transformers by 0.649% per month, so it is estimated that this Transformer 1 at Blimbing Substation has a lifespan of 30 years 9 months. According to IEC 60076-7 normal life of transformers with loading under nominal is 20.55 years or 180000 hours. To minimize loss life of transformer or in other words extend the life time of transformer can be done by scheduling maintenance. Scheduling maintenance is the activity which monitoring the main transmission material on scheduled and provided a treatment based on the monitoring results. It can be concluded that the lifespan of Transformer 1 at Blimbing Substation can exceed the specified standard. The one of factors that affect this, is scheduling maintenance.